(untitled) (Studia Prawnicze / The Legal Studies, 2008)
W prawie rzymskim, które wywarło największy wpływ na rozwój prawa prywatnego i stanowi jego fundament w wielu krajach współczesnego świata, podkreślano, że vis maiorjest to siła, której nie można się oprzeć, lub której nie można było powstrzymać. Natomiast w prawie justyniańskim pojęcie to powiązano z koncepcją najwyższej staranności w sposób uzasadniający stwierdzenie, że siła wyższa jest zdarzeniem zwalniającym od odpowiedzialności dłużnika zobowiązanego do zachowania najwyższej staranności. Wpływ tych koncepcji na kształtowanie się cech siły wyższej w wielu współczesnych systemach prawa jest niewątpliwy. Dotyczy to również prawa wspólnotowego. The aim of the article is to characterise the concept of force majeure in EC Law. It has been taken from the legal systems of the Member States and its evolution in European Community law has been similar to the evolution of the general principles of EC law. However, the European courts have not ruled explicitly that force majeure constitutes one of such principles. Therefore, the question arises how it should be treated - only as an exception to the general rule of the scrupulous compliance with legislative or contract provisions? This problem is dealt in the second section of this study. It is also important to establish how the European Court of Justice (the Court) interprets the notion of force majeure. Its case-law shows that it does not apply only one definition. In fact in its judgements we can find at least four definitions. All of them are presented in the third section of the study together with the examples of the regulations which concern force majeure and are included in different acts of secondary Community law. Apart from the force majeure definition, it is also important to characterise the objective and subjective elements which are combined in this concept. The objective element is connected with the unusual and unforeseeable event which is beyond control of the obliged party. Examples of such events, which come from the judgements of the Court, are presented in the forth section of the study. The case-law also shows when one can say that a person acts with a due care (the subjective element, presented in the fifth section of the study).